2017
DOI: 10.1128/cvi.00236-17
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Epitope Positioning of a Large Collection of Neutralizing and Nonneutralizing Single-Domain Antibodies on the Enzymatic and Binding Subunits of Ricin Toxin

Abstract: We previously produced a heavy-chain-only antibody (Ab) VH domain (V H H)-displayed phage library from two alpacas that had been immunized with ricin toxoid and nontoxic mixtures of the enzymatic ricin toxin A subunit (RTA) and binding ricin toxin B subunit (RTB) (D. J. Vance, J. M. Tremblay, N. J. Mantis, and C. B. Shoemaker, J Biol Chem 288:36538 -36547, 2013, https://doi.org/ 10.1074/jbc.M113.519207). Initial and subsequent screens of that library by direct enzyme-linked immunosorbent assay (ELISA) yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(77 citation statements)
references
References 52 publications
2
75
0
Order By: Relevance
“…To further examine the combinatorial effects of antibodies on ricin toxin neutralizing activity in the LSEC cytotoxicity assay, we turned to a collection of alpaca‐derived single domain antibodies (V H Hs) . V H Hs differ from conventional IgG MAbs in that they are monovalent and are devoid of Fc elements, thereby eliminating any contribution of aggregation and FcR involvement in the cytotoxicity assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further examine the combinatorial effects of antibodies on ricin toxin neutralizing activity in the LSEC cytotoxicity assay, we turned to a collection of alpaca‐derived single domain antibodies (V H Hs) . V H Hs differ from conventional IgG MAbs in that they are monovalent and are devoid of Fc elements, thereby eliminating any contribution of aggregation and FcR involvement in the cytotoxicity assay.…”
Section: Resultsmentioning
confidence: 99%
“…The murine MAbs against RTA (SyH7, PA1, IB2, WECB2, JD4, and PB10) and RTB (MH3, SylH3, LC5, 24B11, 8B3, and 8A1) have been previously described . The V H Hs against RTA (JIVF5, V5E1, V1D3, and V13G5) and RTB (JIZB7, V5D1) have also been described, except for V11E10 (manuscript in preparation) …”
Section: Methodsmentioning
confidence: 99%
“…The nine toxin-neutralizing MAbs that were subjected to epitope mapping in this study (Table 1) were used in a study, reported in a companion paper, of competition ELISAs for the purpose of localizing the binding sites of a large collection of V H Hs (71). As part of that study, we reported the full-length DNA sequences, binding affinities, and neutralizing activities of 31 V H Hs against RTA, 33 against RTB, and 4 against ricin holotoxin.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, we successfully adapted HX-MS for the purpose of identifying epitopes recognized by a family of RTA-specific single-domain alpaca-derived antibodies (V H Hs) (51). We also used HX-MS to assist in epitope refinement of a subset of the 68 V H Hs described in a companion paper (71). We now report the contact points on RiVax recognized by 10 MAbs in epitope clusters I to IV.…”
mentioning
confidence: 99%
“…Clinical and Vaccine Immunology describe the continued mapping of the neutralizing epitopes within ricin toxin (RTX) and relate these studies to current research on the botulinum neurotoxins (BoNTs) (1,2). Our goal is to provide a perspective on how protein structure has facilitated development of vaccines and therapies against regulated select agent (SA) toxins.…”
Section: T His Commentary Addresses Studies By Mantis and Coworkers mentioning
confidence: 99%